Dissolution kinetics of chromite in hydrologic acid solutions - Mena, Manolo G. (Philippine Engineering Journal)
The leaching response of chromite in hydrochloric acid solutions was studied. The results show a 15 to 30 fold enhancement of iron over chromium extraction suggesting the feasibility of chemical beneficiation. The extraction of iron was found to be logarithmic with time. This was explained in terms of the strain relief model involving a linear increase in the leaching activation energy as extraction proceeds.